A preliminary study of genetic landscape of grapevine viruses isolated from a western Georgian vineyard: insights from initial sequencing analysis - Elbakidze, Tinatin; Megrelishvili, Iveta (Journal of Plant Protection Research, 2026)
This study reports the first molecular detection and characterization of four economically important grapevine viruses—Grapevine leafroll-associated virus-1 (GLRaV-1), Grapevine leafroll-associated virus-3 (GLRaV-3), Grapevine fleck virus (GFkV), and Grapevine fanleaf virus (GFLV)—in commercial vineyard of western Georgia. Thirty grapevine samples of the widely cultivated Vitis vinifera cv. Saperavi were collected from a self-rooted vineyard in the Adjara region and analyzed using double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) and one-step RT-PCR. Single and mixed virus infections were detected. Viral presence was further confirmed by Sanger sequencing of partial genomic regions. Sequence analysis revealed high nucleotide identity (88–100%) with grapevine virus isolates previously reported from Europe, North America, and Asia. Phylogenetic analyses conducted in Geneious Prime software revealed that the Georgian isolates clustered among globally distributed reference strains, without forming distinct regional lineages, indicated limited genetic divergence and a conserved population structure. Typical leafroll symptoms were observed only in GLRaV-1- and GLRaV-3-infected vines, whereas GFkV- and GFLV-infected plants remained asymptomatic. These findings provide the first sequence-based evidence of major grapevine viruses spreading in Georgian vineyards, highlighting the need for systematic virus surveillance and the use of certified virus-free planting material to support sustainable viticulture in the country.